Isolation and Characterization of a Bacillus cereus Mutant Strain Hyperproductive of Exo-β-Amylase - Nanmori, Takashi (1987)
Starting with a strain of Bacillus cereus excreting about 40-fold more β-amylase than does the original wild-type strain, we isolated, after mutagenesis with N-methyl-N′-nitro-N-nitrosoguanidine, a strain designated BQ10-S1 SpoIII which showed under optimal conditions a further 5.5-fold increase in β-amylase activity. The amylase production of this strain was observed to increase in the presence of 0.5% glucose or 1% maltose and, more markedly, in the presence of 2% soluble starch in the culture medium. The enzyme produced by this strain was immunologically identical to the wild-type enzyme, suggesting that either the copy number of the gene or the efficiency of enzyme synthesis from it, or both, are altered in this strain.